How ought war to be remembered in schools?. (November 2014) - Aldridge, David
Abstract : Each year a national day of commemoration of the war dead is celebrated on 11th November in the United Kingdom. Despite public controversy about the nature and purpose of remembrance, there has been no significant discussion of the role schools should play in this event. In this centenary year of the outbreak of the First World War, with the government planning to send groups from every secondary school in Britain to tour the battlefields of the western front over the next four years, the question of how war should be remembered in schools is more pressing than ever. In this bold and rigorous pamphlet, David Aldridge takes a hard look at the reasons usually advanced for involving children and young people in commemorating the war dead, and finds many of them wanting. He critically examines the high profile in schools of charities, like the Royal British Legion, with vested interests in certain kinds of commemoration. And he argues forcefully for a justification of remembrance in schools that requires a major rethink of established rituals and practices. This is a compelling treatment of a topic high on the agenda of teachers and education policy‐makers and will be an invaluable resource for anyone involved in planning centenary commemorative events for children and young people.